2020
DOI: 10.1002/aenm.202000064
|View full text |Cite
|
Sign up to set email alerts
|

Robust Swing‐Structured Triboelectric Nanogenerator for Efficient Blue Energy Harvesting

Abstract: Ocean wave energy is a promising renewable energy source, but harvesting such irregular, “random,” and mostly ultra‐low frequency energies is rather challenging due to technological limitations. Triboelectric nanogenerators (TENGs) provide a potential efficient technology for scavenging ocean wave energy. Here, a robust swing‐structured triboelectric nanogenerator (SS‐TENG) with high energy conversion efficiency for ultra‐low frequency water wave energy harvesting is reported. The swing structure inside the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
203
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 290 publications
(204 citation statements)
references
References 39 publications
0
203
0
1
Order By: Relevance
“…31,125 In order to effectively collect the water wave energy, TENGs with various structure design have been proposed, including spring-based structure, 126 wavyelectrode structure, 127,128 duck-shaped structure, 129 rolling spherical structure, 130,131 and air-driven membrane structure, 132 swing structure. 27,133 Spring-based structure is capable of transforming instantaneous mechanical impact energy into elastic potential energy, so that low-frequency output power of the TENG can be improved. Jiang et al designed a spring-assisted TENG for harvesting water wave energy, which is composed of two spring-connected acrylic blocks and an acrylic box ( Figure 10A).…”
Section: Blue Energymentioning
confidence: 99%
See 2 more Smart Citations
“…31,125 In order to effectively collect the water wave energy, TENGs with various structure design have been proposed, including spring-based structure, 126 wavyelectrode structure, 127,128 duck-shaped structure, 129 rolling spherical structure, 130,131 and air-driven membrane structure, 132 swing structure. 27,133 Spring-based structure is capable of transforming instantaneous mechanical impact energy into elastic potential energy, so that low-frequency output power of the TENG can be improved. Jiang et al designed a spring-assisted TENG for harvesting water wave energy, which is composed of two spring-connected acrylic blocks and an acrylic box ( Figure 10A).…”
Section: Blue Energymentioning
confidence: 99%
“…Subsequently, Jiang et al reported a robust swing-structured TENG for efficient blue energy harvesting. 27 An air gap between the triboelectric layers and electrodes, and flexible insulative brushes were employed to reduce the frictional resistance and maintain surface charges, thereby improving the durability and stability of the TENG. Under one triggering, a swing time of 88 seconds can be achieved by the TENG device, and its transferred charge remains nearly unchanged after 400 000 cycles.…”
Section: Blue Energymentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] Recently, TENG has reached an energy harvesting efficiency of 28% by triggering in water. [18] In conclusion, we presented a summary about the fundamentals related to TENG. This is a new invention, and it is anticipated to have many unique applications in fields such…”
Section: Figure Of Merits Of Tengmentioning
confidence: 99%
“…[ 16,17 ] Recently, TENG has reached an energy harvesting efficiency of 28% by triggering in water. [ 18 ]…”
Section: Technological Impacts Of Tengmentioning
confidence: 99%